Copyright Protection Reform for Traditional Cultural Expressions: Confirming the Status and Position of Communities - Muhammad Fahrial Amrulla; Afifah Kusumadara; Budi Santoso; Yenny Eta Widyanti (PATTIMURA Legal Journal, 2026)
Introduction: Traditional batik motifs are one of the traditional cultural expressions that are the object of intellectual property law protection. The social, cultural, moral, and spiritual values ​​contained in traditional batik motifs are a cultural heritage passed down from generation to generation and are sacred. In Indonesian positive law, protection of traditional cultural expressions is stipulated in the Copyright Law and the Government Regulation on Communal Intellectual Property. Purposes of the Research: This research will focus on the review of copyright protection for traditional cultural expressions held by the state. Furthermore, this study will also discuss the importance of implementing FCIP principles in ensuring the involvement of indigenous communities in decision-making. Methods of the Research: The method used in this study is doctrinal legal research using legislative and conceptual approaches. The collection of legal materials in this study uses a literature study. Results Main Findings of the Research: Copyright protection for traditional cultural expressions is held by the state. However, in its implementation, the concept of protecting traditional cultural expressions held by the state lacks clear regulations regarding its technicalities and mechanisms. The existence of the state as the holder of copyright degrades the ownership status of traditional cultural expressions by communal communities. The minimal participation of communal communities in decision-making also indicates weaknesses in the legal protection of traditional cultural expressionsThe state's guardianship of copyright over traditional cultural expressions has weaknesses and requires reform by changing the protection mechanism to a legal protection manager by strengthening the application of FCIP principles.